PERILAKU PENCEGAHAN STUNTING: TINJAUAN DUKUNGAN KELUARGA DAN UPAYA PROMOSI KESEHATAN - Juniarti, Rizky Auliah; Wahyuni, Emmy Putri; Sudarman, Dirman; Kristina, Yunita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Nutrition issues in Indonesia remain one of the top priorities in the national health development agenda, particularly efforts to control stunting. Stunting cases in West Java Province remain high and constitute one of the nutrition issues requiring serious attention. The objective of this study is to determine the relationship between family support and health promotion efforts on stunting prevention behavior. The research design used in this study is cross-sectional. The study was conducted in Dramaga District in July 2024. The population consisted of all families with infants, totaling 300 households. The sample size was 87 respondents. The sampling technique used was Simple Random Sampling. The research instrument was a questionnaire. Data analysis was performed using univariate and bivariate methods. The results of the study indicate a relationship between family support (p-value: 0.014) and health promotion efforts (p-value: 0.032) and stunting prevention behavior. It is recommended that health workers enhance education on stunting, the importance of family support, and stunting prevention methods by conducting more frequent prenatal classes and providing education during prenatal check-ups to help reduce stunting rates.Keywords: Family Support, Health Promotion, Stunting/